Carrier-Based Obturation: Effect of Sonication Technique on Sealer Penetration in Dentinal Tubules: A Confocal Laser Scanning Microscope Study - Riccardo Tonini; Matteo Salvadori; Marco Bartoli; Jacopo Francinelli; Paolo Bertoletti; Maria Luisa Garo; Stefano Salgarello (Applied Sciences, 2022)
(1) Background: In endodontics, anatomical complexities and irregularities in the root canal system may interfere with sealer penetration, increasing the risk of treatment failure. This work aimed to investigate the effects of sonicated Thermafil (Dentsply, Tulsa Dental Specialties, Johnson City, TN, USA) on sealer penetration into the dentinal tubules. (2) Methods: Thirty teeth with single round-shaped root canals were used to compare Sonicated Thermafil with sonication (ST—10 teeth), System B (EIE Analytical Technology, Orange, CE, USA) (SB—10 teeth), and Thermafil without sonication (T—10 teeth). A confocal laser scanning microscope (CLSM) was used to determine the depth, area, and percentage of sealer penetration into the dentinal tubules. (3) Results: ST showed the deepest average penetration at 6 mm from the apex compared to SB (p < 0.01) and T (p < 0.01) and at 3 mm compared to SB (p < 0.01). In addition, it had the highest penetration values at both levels compared to SB (p < 0.01) and T (p < 0.05) and a higher penetration area at 6 mm compared to T (p < 0.05) and SB (p < 0.05). (4) Conclusion: Sonic activation can improve the carrier-based obturation technique thanks to deeper sealer penetration and thus better retention of materials.